TOWARD QUALITY CONTROL OF BIOGAS PRODUCT IN INDONESIA: AN OVERVIEW - Oman Zuas; Eka Mardika Handayani; Muhammad Rizky Mulyana; Melati Azizka Fajria; Harry Budiman; Ayu Hindayani; Arfan Sindhu Tistomo; Anthoni Batahan Aritonang; Nazarudin Nazarudin (Indonesian Journal of Pure and Applied Chemistry, 2021)
The quality control of the final product of biogas is essential for providing a maximum level of consumer’s satisfaction. The most important criteria for any biogas product are its regulatory compliance and safety. Based on a desk study of document and laboratory experiment, this paper overviews the development of infrastructure of quality to control the quality of biogas, aiming at summarising the experience, problems and demonstrating development status of quality infrastructure in Indonesia in the hope of providing references for the present condition. The discussion is made to cover issues related to biogas that are emphasized on three pillars of the infrastructure of quality in Indonesia, i.e., standardization, metrology, and conformity assessment. From the overview, the critical conclusion where understanding and continuing the development quality infrastructure of assuring the safety and quality of biogas remain essential.